2019
DOI: 10.3390/foods8070242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antioxidant Activity of Products Derived from Xylose–Bovine Casein Hydrolysate Maillard Reaction: Impact of Reaction Time

Abstract: The characterization and antioxidant activity on Maillard reaction products (MRPs) derived from xylose and bovine casein hydrolysate (BCH) was investigated at 100 °C and initial pH 8.0 as a function of reaction time. The pH values and free amino groups contents of xylose–BCH MRPs remarkably decreased with the reaction time up to 8 h, whereas their browning intensities significantly increased (p < 0.05). After 4 h of heat treatment, the fluorescence properties of xylose–BCH MRPs reached the maximum. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
7
13
1
Order By: Relevance
“…No significant change in TPC was observed in WF cookies with reduced sucrose addition compared to the control WF cookies. The AOA decreased with decreasing sucrose content from 7.3 to 3.5% in WF cookies without added sucrose, suggesting that the Maillard reaction products and the caramelization products formed from sucrose after thermal hydrolysis during baking have some antiradical properties and reducing potential, as reported by other authors [ 62 , 63 , 64 , 65 ]. Given the results obtained from the AOA of MBF:WF cookies, it can be concluded that the inclusion of MBF in the cookie recipe can improve the nutritional properties and health benefits of the product.…”
Section: Resultssupporting
confidence: 73%
“…No significant change in TPC was observed in WF cookies with reduced sucrose addition compared to the control WF cookies. The AOA decreased with decreasing sucrose content from 7.3 to 3.5% in WF cookies without added sucrose, suggesting that the Maillard reaction products and the caramelization products formed from sucrose after thermal hydrolysis during baking have some antiradical properties and reducing potential, as reported by other authors [ 62 , 63 , 64 , 65 ]. Given the results obtained from the AOA of MBF:WF cookies, it can be concluded that the inclusion of MBF in the cookie recipe can improve the nutritional properties and health benefits of the product.…”
Section: Resultssupporting
confidence: 73%
“…In order to limit or prevent the Maillard reaction it is recommended to carry out the process of conching milk masses at a temperature not exceeding 50 • C [9]. The Maillard reaction is affected by many aspects, including temperature, pH, water content, duration of heating, type of reactant, oxygen, ratio of amino acid to sugar, metals, and reaction inhibitors [20].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the physiological role of melanoidins present in many heat-treated foods has increased dramatically over the last decade, particularly in relation to human health [2,9,10]. The biological effects exerted by melanoidins on the human body are thought to be strongly related to their ability the chelate metal cations, the capacity of scavenging superoxide anions and hydroxyl radicals, and the decomposing ability of hydrogen peroxide [10,11], which may be responsible for the antioxidant, anticancer, and antimicrobial properties [12]. Food melanoidins can also act as dietary fiber in the gastrointestinal tract and promote the growth of beneficial Bifidobacteria in the gut [9,11].…”
Section: Introductionmentioning
confidence: 99%